Evaluation of a multidisciplinary burn care journal club: Lessons learned. Issue 3 (May 2018) - Carta, T.; Gawaziuk, J.P.; Cristall, N.; Forbes, L.; Logsetty, S.
Highlights: Multidisciplinary journal clubs provide team based learning and skill development. Journal clubs can start with lunch and learn sessions and evolve over time. Participants liked facilitated discussion in burn journal club. Identify champions from each discipline early to act as facilitators. Evaluation tools assist in the assessment of articles and group discussion. Abstract: Background: Journal clubs allow discussion of the quality and findings of recent publications. However, journal clubs have not historically been multidisciplinary. Burn care is recognized as a true collaborative care model, including regular multidisciplinary rounds. Since 2011 we have offered a multidisciplinary burn journal club at our institution. We present an evaluation of the factors that have made the sessions successful to facilitate others to commence their own club. Methods: At the end of each journal club session participants anonymously completed a structured evaluation. Five-point scales were used to evaluate understanding, meeting objectives, presentation and appropriateness of information. Qualitative questions were asked to identify beneficial factors, suggestions for improvements, ideas for future sessions and feedback for the facilitator. Results: Attendance grew from six to a maximum of 19. Members included physicians, nurses, dieticians, physiotherapists, occupational therapists, social workers, basic scientists and students. Presentations were undertaken by all of these disciplines. Ratings improved steadily over time. Understanding increased from a score of 4.5 to 4.8; meeting objectives from 4 to 4.9; satisfaction with method of presentation from 4.3 to 4.9 and with level of information from 3 to 4.9. Conclusions: Over time, the journal club has evolved to better meet the needs of our team. Successful multidisciplinary journal club implementation requires identification of champions and ongoing evaluation. Applicability of research to practice: The success of the journal club has been possible through the engagement of the entire burn team. Champions within each discipline, facilitated discussion and evaluation tools have helped nurture a nonthreatening team based learning environment.